Elites legislativas federais e locais no Brasil: uma discussão teórica sobre formação, permanência e representatividade no poder - Costa, Mariana Plácida de Faria (Universidade Federal de São Carlos, 2025)
This work theoretically discusses the differences between federal and local legislative elites in Brazil, focusing on the processes of formation, recruitment, permanence, and political action. Based on classical elite theories (Pareto, Mosca, and Michels) and contemporary reformulations (C. Wright Mills and Pierre Bourdieu), the research aims to understand how different forms of political, symbolic, economic, and social capital operate in structuring legislative elites in distinct contexts. The bibliographic review method, proposed by authors such as Gil (2008), Minayo (2001), and Codato (2018), is used to systematize relevant academic production on the subject. Brazilian authors such as Maria Teresa Kerbauy, Octaciano Nogueira, Bruno Speck, and César Zucco Jr. are mobilized to highlight the specificities of parliamentary action at different institutional levels. The analysis reveals distinct patterns of professionalization, recruitment, and power strategies, highlighting the implications of these differences for political representativeness and the functioning of democracy in the country.
Federal and local legislative elites in Brazil: a theoretical discussion on formation, retention, and representativeness in power
Keywords: Elites políticas; Legislativo; Federal; Local; Representatividade; Political elites; Legislature; Federal; Representativeness; CIENCIAS HUMANAS::CIENCIA POLITICA::TEORIA POLITICA; 9. Indústria, Inovação e Infraestrutura